Commitment Requests Do Not Affect Truth-Telling in Laboratory and Online Experiments - Tobias Cagala; Ulrich Glogowsky; Johannes Rincke; Simeon Schudy (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Using a standard cheating game, we investigate whether the request to sign a no-cheating declaration affects truth-telling. Our design varies the content of a no-cheating declaration (reference to ethical behavior vs. reference to possible sanctions) and the type of experiment (online vs. offline). Irrespective of the declaration's content, commitment requests do not affect truth-telling, neither in the laboratory nor online. The inefficacy of commitment requests appears robust across different samples and does not depend on psychological measures of reactance.
Keywords: C91; C93; D03; 330; cheating; lying; truth-telling; compliance; commitment; no-cheating rule; no-cheating declaration; commitment request